APPLICATION OF SIX SIGMA METHOD TO REDUCE DEFECT RATE IN BREAD PRODUCTION - Ikhsan Nurrobbil, Damar; Roder, Klause (Pena Cendekia Insani, 2024)
This research discusses the application of the Six Sigma method with the DMAIC approach to reduce the defect rate of bread products at Fadillah Bakery. Through seven days of observation, 248 defective products were found from 2.100 samples with an average Defect Per Million Opportunities (DPMO) of 118.095,2 and asigma level of 2,19. The analysis showed that the factors causing product defects include human error (lack of training and accuracy), non-optimal work methods, and improper roasting machine settings. The proposed improvement measures include increased worker training, scheduling machine maintenance, and stricter supervision. The proposed improvement measures included increased worker training, scheduling machine maintenance, and stricter supervision. The results prove that the implementation of Six Sigma is effective in reducing defect rates, improving product quality, and production process efficiency. Continued implementation is expected to improve Fadillah Bakery's competitiveness and customer satisfaction of Fadillah Bakery.